Persepsi Mahasiswa terhadap Metode Cooperative Learning dengan Memanfaatkan Blogspot pada Keterampilan Menulis - Icha Fina Fanesha; Ira Suciarti; Daroe Iswatiningsih (Klitika: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2023)
One of the web information that can support the learning process of cooperative learning is to use the Blogspot media. This study aims to describe (1) describing student perceptions of the cooperative learning method by utilizing Blogspot in writing skills and describing (2) the benefits of Blogspot in learning media for students. The type of research used is quantitative research. The data used in the form of responses from Indonesian Language Education students to the cooperative learning method by utilizing Blogspot on writing skills. The form of the data obtained is in the form of distributing questionnaires to 35 students of the University of Muhammadiyah Malang as a sample of students of the Indonesian Language Education Study Program. The data analysis technique uses quantitative descriptive analysis, namely an analysis that provides an overview or descriptive of a situation objectively using diagrams and numbers starting from data collection, interpretation of the data as well as appearance and results. The results showed that 100% of students knew that Blogspot media was often used in the learning process, but there were some difficulties experienced by students, namely they did not understand when using blog media as writing skills with a percentage of 60%. One of the benefits of using blog media is that blogs are used to collect discussion results, so that readers can provide comments and suggestions. The conclusion of the research shows that students use blog media in certain learning, the aim is to train writing skills, and can develop cooperative learning methods in the learning process carried out and the benefits obtained in using the Blogspot media.